1986
DOI: 10.1111/j.1749-6632.1986.tb18549.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Chronic Sarcoidosis with Low‐Dose Maintenance Corticosteroid Therapy

Abstract: A series of 181 patients with chronic persistent sarcoidosis for more than 5 years have been reviewed, with a mean follow-up period of 14 years, and 77% followed for more than 10 years. Efforts to identify more white patients meeting the criteria of such persistent disease were unsuccessful. Seventy-eight percent were black, and 69% were women. Pulmonary disease was the major manifestation in 70% and was present in 88%. The early major disease feature predicts the nature of the long-term manifestation in 94%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 7 publications
1
50
0
2
Order By: Relevance
“…Once treatment with corticosteroids is started, it is acceptable to complete at least 6–12 months of therapy. About 90% of the patients treated with corticosteroids respond favorably by improvement of symptoms, pulmonary function tests, and radiologic findings, and 60% remain in complete remission following withholding corticosteroids [2]. It is suggested that the rate of recurrence after discontinuation of corticosteroids may decrease as the initial course of corticosteroid therapy is more prolonged [3].…”
Section: Discussionmentioning
confidence: 99%
“…Once treatment with corticosteroids is started, it is acceptable to complete at least 6–12 months of therapy. About 90% of the patients treated with corticosteroids respond favorably by improvement of symptoms, pulmonary function tests, and radiologic findings, and 60% remain in complete remission following withholding corticosteroids [2]. It is suggested that the rate of recurrence after discontinuation of corticosteroids may decrease as the initial course of corticosteroid therapy is more prolonged [3].…”
Section: Discussionmentioning
confidence: 99%
“…34 In contrast to this, some studies from the United States and British Isles cite a disproportionate representation of radiographic stage III and IV disease. [35][36] Previous studies from India 6,8 report that most of the radiographic abnormalities belonged to stage I and II, 21, 37 but another study 26 found that stage II and III were more common. 38 In present study, the most common stage of sarcoidosis on presentation was found to be stage II (46.6 %) followed by stage I (40%).…”
Section: Resultsmentioning
confidence: 99%
“…If a relapse occurs, as evidenced by reappearance of clinical signs, chest radiographic abnormalities or lung function impairment, prednisone levels are then increased to a dosage sufficient to control the disease and subsequently tapered to a maintenance dose that is likely to be higher than the dose at which the relapse occurred. It has been shown that almost all of these relapses occur within 1-2 months of steroid therapy withdrawal, and three-quarters of patients who require corticosteroids for o5 yrs relapse when corticosteroids are withdrawn [92]. Of these patients, .90% can be maintained on a regimen of f15 mg prednisone daily, and 65% on f10 mg [92].…”
Section: Local Protocolmentioning
confidence: 99%
“…It has been shown that almost all of these relapses occur within 1-2 months of steroid therapy withdrawal, and three-quarters of patients who require corticosteroids for o5 yrs relapse when corticosteroids are withdrawn [92]. Of these patients, .90% can be maintained on a regimen of f15 mg prednisone daily, and 65% on f10 mg [92]. Although an alternate-day regimen is effective, with considerable reduction in side-effects, daily treatment is recommended because of the increased compliance [93].…”
Section: Local Protocolmentioning
confidence: 99%